Improved Thin-Walled Finite Curved Beam Elements - Nam-Il Kim; Chan-Ki Jeon (Advances in Mechanical Engineering, 2013)
The two- and three-noded spatially coupled thin-walled finite curved beam elements are presented on the basis of assumed strain fields. These elements consider the extensional/inextensional conditions along the centroid axis of curved beam. For curved beams with the extensional condition, the two-noded element is formulated from constant strain and linear curvature fields. And the strain is assumed as linear filed and curvatures are assumed to be third-order ones for the three-noded element. In addition the normal stress at an arbitrary point of symmetric and non-symmetric cross-sections is explicitly evaluated since strain and curvature functions are assumed independently. In order to illustrate the accuracy and the practical usefulness of the present assumed strain curved beam elements, the displacements and the normal stresses of curved beams are evaluated and compared with the previously published results and the solutions by the shell elements from SAP 2000. The emphasis is given in investigating the influence of inextensibility along the beam axis on the coupled behavior of curved beam with respect to the values of boundary condition, subtended angle, and slenderness ratio.